A Educação matemática & ensino fundamental: um panorama das pesquisas produzidas na PUC/SP nos anos 1994 a 1997 - Perreira, Luciane Maciel Xavier de Oliveira (2003)
The present work aimed to analyze the dissertations about The Teaching in Elementary School, produced in the Program of Post-Graduate Studies of Mathematics Education at a Catholic University Pontifícia Universidade Católica de São Paulo, in the period from 1994 to 1997. After the analysis of the eight dissertations, it was possible to categorize them in relation to the chosen objective of the research. The attained results allowed to conclude that the preferences in the research were the contents worked in the classroom and they were divided into the teacher and student s point of view, and fifty percent of these papers (dissertations) have chosen as theme the numbers and their operations. Beside this, most of the papers (seven) have tried to create a situation in where they could develop a significance to the chosen Mathematics notions